2016
DOI: 10.1007/s00429-016-1323-9
|View full text |Cite
|
Sign up to set email alerts
|

Interhemispheric resting-state functional connectivity of the claustrum in the awake and anesthetized states

Abstract: The claustrum is a brain region whose function remains unknown, though many investigators suggest it plays a role in conscious attention. Resting-state functional magnetic resonance imaging (RS-fMRI) has revealed how anesthesia alters many functional connections in the brain, but the functional role of the claustrum with respect to the awake versus anesthetized states remains unknown. Therefore, we employed a combination of seed-based RS-fMRI and neuroanatomical tracing to reveal how the anatomical connections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 97 publications
(190 reference statements)
3
54
0
Order By: Relevance
“…However, unlike prior studies, which largely relied on variations of depth of anesthesia, our comparison of awake states and anesthesia also suggested that the visual networks and their connectivity with default and frontoparietal networks actually showed anesthesia-related increases in connectivity. Overall, these findings echo recent studies of the impact of anesthetics on brain differences in humans, which suggested a loss of complexity in the functional architecture of the brain (Chang et al, 2016; Hutchison et al., 2014; Peltier et al, 2005; Smith et al, 2017; Wu et al, 2016). Further work will be required to rule out other possibilities, such as differences in respiration associated with differing states (awake or anesthesia).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, unlike prior studies, which largely relied on variations of depth of anesthesia, our comparison of awake states and anesthesia also suggested that the visual networks and their connectivity with default and frontoparietal networks actually showed anesthesia-related increases in connectivity. Overall, these findings echo recent studies of the impact of anesthetics on brain differences in humans, which suggested a loss of complexity in the functional architecture of the brain (Chang et al, 2016; Hutchison et al., 2014; Peltier et al, 2005; Smith et al, 2017; Wu et al, 2016). Further work will be required to rule out other possibilities, such as differences in respiration associated with differing states (awake or anesthesia).…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have demonstrated that FC patterns are sculpted more by structural connectivity under deep anesthesia than the awake state (Barttfeld and Uhrig, 2015; Wu et al, 2016). In anesthesia states, when isoflurane levels were varied, the signal fluctuations and connectivity also exhibited distinct profiles at each level within the same animal (Smith et al, 2017; Gao et al, 2017; Peltier et al, 2005; Hutchison et al., 2014). While it is expected that the parcels revealed will in many cases exhibit a gross similarity to traditionally defined neocortical areas, they are not intended to be 1:1.…”
Section: Discussionmentioning
confidence: 99%
“…The terminal boutons of claustrocortical projections are very small with a morphology that has been suggested to resemble “modulator” type synapses. As shown in the photomicrograph in Figure d, these terminals appear as small (<0.5 ÎŒm diameter), “mushroom‐like” boutons that extend off the axon (da Costa et al, ; Smith et al, ), which is consistent with “modulator” type synapses that exhibit paired‐pulse facilitation on their postsynaptic targets (Sherman & Guillery, ). However, there is some controversy surrounding the “driver/modulator” categorization for claustral synapses, especially for corticoclaustral synapses (Brown et al, ; Day‐Brown et al, ).…”
Section: Reassessing the Relationship Of The Cla And En In Rodentsmentioning
confidence: 60%
“…boutons that extend off the axon (da Costa et al, 2010;Smith et al, 2017), which is consistent with "modulator" type synapses that exhibit paired-pulse facilitation on their postsynaptic targets (Sherman & Guillery, 1998). However, there is some controversy surrounding the "driver/modulator" categorization for claustral synapses, especially for corticoclaustral synapses Day-Brown et al, 2017).…”
Section: Laminar Organization Of Connectivity Between Cla-den and Cmentioning
confidence: 69%
See 1 more Smart Citation